Intrinsic interaction inferred oxidative stress and apoptosis by Biosurfactant-microplastic hybrid reduces coordinated in vivo biotoxicity in zebrafish (Danio rerio) - Utsa Saha; Aishee Ghosh; Adrija Sinha; Aditya Nandi; Sudakshya S. Lenka; Abha Gupta; Shalini Kumari; Anu Yadav; Mrutyunjay Suar; Nagendra Kumar Kaushik; Vishakha Raina; Suresh K. Verma (Materials Today Bio)
The proliferation of microplastics (μP) in aquatic environments poses a significant threat to ecosystem health, with repercussions extending to aquatic organisms and potentially to human health. In this study, we investigated the efficacy of a novel biosurfactant-microplastic (BSμP) hybrid in reducing in vivo green bio-toxicity of microplastics (μP) induced by oxidative stress and apoptosis in zebrafish (Danio rerio). Microplastics, ubiquitous in aquatic environments, were hybridised with Biosurfactant to evaluate their potential mitigating effects. A stable BSμP was formed with zeta potential of −10.3 ± 1.5 mV. Exposure of zebrafish embryos to μP resulted in increased oxidative stress markers, including elevated levels of reactive oxygen species and induced apoptosis, as evidenced by increased expression of apoptotic markers and morphological changes in embryonic zebrafish. However, the BSμP hybrid significantly ameliorated the observed toxic effects with reduced levels of oxidative stress markers and apoptotic activity. This effect was deduced as the intrinsic effects of hybridisation, which likely mitigated the bioavailability and toxicity of μP by reducing their molecular interaction with metabolic proteins like Sod1 and p53 through less accumulation and internalisation. Overall, our findings highlight the potential of BSμP as a promising approach for mitigating the ecological impacts of microplastic pollution.